Productive and reproductive performance and reproductive health problems of Begait breed cows under farmers’ management in and around Seharti Samre, South East zone of Tigray regional state, Ethiopia - Gebreyohannes, Gebrehiwet; Gebrewahd, Tsegay Tkue; Mebratu, Awot Teklu (Nigerian Journal of Animal Science, 2023)
A survey was carried out on productive and reproductive performance and reproductive health problems of Begait cows under farmers’ management in and around Seharti Samre. Accordingly, 93 farmers were selected randomly for interview, and 123 Begait breed cows at parity one and two were selected to assess productive and reproductive performance as well as reproductive health problems. Data were obtained from the farmers by using pre-tested, structured questionnaire. Majority (96.8%) of the farmers were males with farming experience from 1-10 years (58.1%) All (100%) of the farmers were engaged in mixed crop-livestock production, and crop production was found to be the main source of income for 92.5% of them. The reproductive performances were: age at first service (27.12 ± 0.387 months), age at first calving (36.27 ± 0.424 months), number of services per conception (1.07 ± 0.24), calving interval (18.54 ± 0.569 months) and days open (9.97 ± 0.54 months). The productive performances were: lactation milk yield (605.85 ± 20.793 liters) and lactation length (6.96 ± 0.126 months). The reproductive health problems were: calf mortality (92.5%), anestrus (82.8%), repeat breeding (74.2%), uterine prolapse (62.4%), dystocia (57%), abortion (55.9%) and retained placenta (44.1%).